The contribution of neutral evolution and adaptive processes in driving phenotypic divergence in a model mammalian species, the Andean fox Lycalopex culpaeus. (6th March 2018) - Martinez, Pablo A.; Pia, Monica V.; Bahechar, Ilham A.; Molina, Wagner F.; Bidau, Claudio J.; Montoya‐Burgos, Juan I.
Abstract: Aim: Understanding the mechanisms that drive phenotypic divergence along climatic gradients is a long‐standing goal of biogeography. To fulfil this objective, we tested if neutral and/or adaptive effects drive phenotypic diversification. We quantified the effects of neutral evolution and natural selection on morphological variability of a well‐suited mammalian species, the fox, Lycalopex culpaeus . Location: South America. Methods: We analysed variations in skull shape, jaw shape and skull size in L. culpaeus . The processes underlying our models were: local adaptation, and short‐ or long‐term neutral evolution. We inferred genetic population structure using mitochondrial and nuclear markers, we quantified morphological differences among populations by performing geometric morphometric analyses, and we inferred an ecological niche model for calculating environmental resistance between populations. Results: We identified six genetically differentiated populations of the Andean fox, which correspond well to the described subspecies. We showed that skull shape variation is explained by population structure. Skull size showed a clear Bergmannian pattern with larger animals in higher latitudes (in absolute values). Skull size divergence is driven by the combined effects of environmental factors and population structure. Intriguingly, none of the models explains the variation observed in jaw shape. Main Conclusion: Population phenotypic variation in the Andean fox L. culpaeus is driven by deterministic and neutral processes. The methodological framework presented here opens up new opportunities to study phenotypic evolution; it allowed us to demonstrate that the processes explaining trait variation can differ among traits and to show empirically for the first time that a trait can diverge among populations due to simultaneous adaptation and neutral evolution.